Novel anti-pseudomonas cephalosporins - Chang, MH; Koh, HY; Cho, YS; Choi, KI (BENTHAM SCIENCE PUBL BV, 1997)
Since the catechol type cephalosporins having a potent activity against P. aeruginosa strain were introduced, many kinds of derivatives have been developed. These cephalosporins adopted various substituents as siderophores such as catechol or pyridone type derivatives at C-7 or C-3 position to facilitate their penetration through the bacterial cell membrane. In this review, the structural specifications of the recently developed cephalosporins and their biological activity against P. aeruginosa bacterial strain would be overviewed.
Keywords: ANTIBACTERIAL ACTIVITY; SYNTHETIC CEPHALOSPORINS; CATECHOL MOIETY; C-7; POSITION; ACID